Actin capping protein alpha maintains vestigial-expressing cells within the Drosophila wing disc epithelium. - Janody, F.; Treisman, J.E. (Development, 2006)
Tissue patterning must be translated into morphogenesis through cell shape changes mediated by remodeling of the actin cytoskeleton. We have found that Capping protein alpha (Cpa) and Capping protein beta (Cpb), which prevent extension of the barbed ends of actin filaments, are specifically required in the wing blade primordium of the Drosophila wing disc. cpa or cpb mutant cells in this region, but not in the remainder of the wing disc, are extruded from the epithelium and undergo apoptosis. Excessive actin filament polymerization is not sufficient to explain this phenotype, as loss of Cofilin or Cyclase-associated protein does not cause cell extrusion or death. Misexpression of Vestigial, the transcription factor that specifies the wing blade, both increases cpa transcription and makes cells dependent on cpa for their maintenance in the epithelium. Our results suggest that Vestigial specifies the cytoskeletal changes that lead to morphogenesis of the adult wing.